Mast cell tissue heterogeneity and specificity of immune cell recruitment - West, Peter W.; Bulfone-Paus, Silvia (Frontiers in Immunology, 2022)
Mast cells have been recognised to be distinct and highly variable between and within tissues. However, the impact of mast cell tissue heterogeneity on the interaction with other immune cells and on defined immune responses is still unclear. In this review, we synthesize the characteristics of mast cell heterogeneity in the gut and the skin. Furthermore, we attempt to connect mast cell heterogeneity with functional diversity by exploring differences in mast cell-induced immune cell recruitment in these two model organs. The differential expression of certain receptors on mast cells of different tissues, notably tissue-specific expression patterns of integrins, complement receptors and MRGPRX2, could indicate that tissue environment-dependent factors skew mast cell-immune cell interactions, for example by regulating the expression of these receptors.